Theory of Mind and Sociometric Peer Status: The Mediating Role of Social Conduct - Lonigro, Antonia; Baiocco, Roberto; Pallini, Susanna; Laghi, Fiorenzo (Frontiers in Psychology, 2018)
The present study aimed at investigating the mediating role of social conduct in the relation between theory of mind (ToM) and sociometric peer status. One hundred and seventy-seven 8- to 11-year-olds filled out a battery encompassing advanced ToM skill, verbal ability and sociometric peer status, expressed in terms of social preference and social impact. A questionnaire on students' externalizing, internalizing and prosocial behaviors was administered to teachers. Only externalizing behavior mediated the link between ToM and social impact, controlling for age, gender, and verbal ability. Implications and suggestions for future research were discussed.